Circulating adrenaline and noradrenaline concentrations during exercise in patients with exercise induced asthma and normal subjects. Issue 4 (April 1988) - Berkin, K E; Walker, G; Inglis, G C; Ball, S G; Thomson, N C
Abstract : A failure of the usual increase in plasma adrenaline and noradrenaline concentrations during submaximal exercise has been suggested as a contributory cause of exercise induced asthma. Six normal subjects and six asthmatic patients underwent a standard graded maximal exercise test. Measurements of oxygen consumption, minute ventilation, exercise time, blood lactate concentration, and heart rate indicated that the two groups achieved similarly high work loads during exercise. Mean FEV1 fell by 20% in asthmatic patients after exercise. Basal plasma adrenaline concentrations (nmol/l) increased in normal subjects from 0.05 to 2.7 and in asthmatic patients from 0.12 to 1.6 at peak exercise. Noradrenaline concentrations (nmol/l) increased in normal subjects from 2.0 to 14.3 and in asthmatic patients from 1.9 to 13.7 at peak exercise. The increases in adrenaline and noradrenaline in the asthmatic patients did not differ significantly from the increases in normal subjects. Thus a reduced sympathoadrenal response to exercise seems unlikely to be an important mechanism in the pathogenesis of exercise induced asthma.